2013
DOI: 10.1093/ndt/gft018
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the sub-optimal dialysis starter on peritoneal dialysis. Report from the French Language Peritoneal Dialysis Registry (RDPLF)

Abstract: A B S T R AC TBackground. This study was carried out to examine the association of sub-optimal dialysis initiation of peritoneal dialysis (PD) with all the possible outcomes on PD using survival analysis in the presence of competing risks. Methods. This was a retrospective cohort study based on the data of the French Language Peritoneal Dialysis Registry. We analysed 8527 incident patients starting PD between January 2002 and December 2010. The end of the observation period was 01 June 2011. Times from the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Even if we assume that part of these respondents underestimated this time period [12], still for many of them the time would be considered too short for optimal preparation of the patient, e.g., to create an arterio-venous fistula. However, several authors have demonstrated that in centres with dedicated programmes, free modality choice can be offered despite late referral [21][23]. Future research may explore the availability of such programmes across Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Even if we assume that part of these respondents underestimated this time period [12], still for many of them the time would be considered too short for optimal preparation of the patient, e.g., to create an arterio-venous fistula. However, several authors have demonstrated that in centres with dedicated programmes, free modality choice can be offered despite late referral [21][23]. Future research may explore the availability of such programmes across Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the PD studies were cohort studies [48-57], three were non-comparative [58-60] and one used cross sectional study design [61]. Five national level PD cohort studies [48,51,52,55,56] used information from the French Language Peritoneal Dialysis Registry (RDPLF). Two of these RDPLF studies [51,52] used the same time period but applied different exclusion criteria based on the focus of the studies .…”
Section: Resultsmentioning
confidence: 99%
“…Five national level PD cohort studies [48,51,52,55,56] used information from the French Language Peritoneal Dialysis Registry (RDPLF). Two of these RDPLF studies [51,52] used the same time period but applied different exclusion criteria based on the focus of the studies . Two PD cohort studies [53,54] relied on data from regional dialysis units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations